Ellipse - Double-Duty - weiterwirkendes Wort (wW) im biblischen Hebräisch: Verbalsyntaktische und stilistische Beobachtungen - Groß, Walter (Biblica, 2022)
This article investigates a stylistic device of classical Hebrew that had already been recognized by Jewish grammarians in Medieval times and has been treated as double duty by Mitchell Dahood since 1965, which has initiated significant discussion in research. For the first time, this study points to possible consequences of double duty on the form of the verbal predicate in prose and, especially, poetry of classical Hebrew. Many occurrences that have hitherto been considered infringements of rules or interpreted, not aligned with the classical Hebrew verbal system, as perfectum/imperfectum copulativum, thus prove conforming to rule. They are analysed as stylistic variants, which require an explanation of their stylistic effect.